HUBUNGAN KETERAMPILAN MEMBACA KRITIS DENGAN KETERAMPILAN MENULIS ARTIKEL POPULER SISWA KELAS XI SMA NEGERI 5 PADANG - Najmi Hayati (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2017)
This study aimed to describe the relationship of critical reading skills with popular article writing skills class XI student of SMAN 5 Padang. The study population was a class XI student of SMAN 5 Padang. The sampling amounted to 30 students is done by proportional random sampling. Data collected through an objective test and test performance. Objective test is used to determine the results of critical reading skills, test performance was conducted to determine the results of the popular article writing skills. Analysis and discussion of the data is a descriptive correlational to know the great relationship of critical reading skills with popular article writing skills. Based on the results of the study concluded the following three. First, the level of critical reading skills class XI student of SMAN 5 Padang quite enough (67.23). Second, popular article writing skill level class XI student of SMAN 5 Padang is quite (64.7). Third, there is a significant relationship between critical reading skills with popular article writing skills class XI student of SMAN 5 Padang 0.466.